2021
DOI: 10.1007/s10347-021-00627-y
|View full text |Cite
|
Sign up to set email alerts
|

Depositional setting and limiting factors of early Late Cretaceous glaucony formation: implications from Cenomanian glauconitic strata (Elbtal Group, Germany)

Abstract: Cenomanian strata of the Elbtal Group (Saxony, eastern Germany) reflect a major global sea-level rise and contain, in certain intervals, a green authigenic clay mineral in abundance. Based on the integrated study of five new core sections, the environmental background and spatio-temporal patterns of these glauconitic strata are reconstructed and some general preconditions allegedly needed for glaucony formation are critically questioned. XRD analyses of green grains extracted from selected samples confirm thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…2015; Glad et al . 2018; Wilmsen & Bansal, 2021). To supplement the facies analysis in the Kalshaneh outcrop, a core of an exploration borehole, focused on coal seams in the lowermost part of the Hojedk Formation, near to the measured outcrop section, was incorporated into this study to better characterize the facies and their vertical relationship and lateral variations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2015; Glad et al . 2018; Wilmsen & Bansal, 2021). To supplement the facies analysis in the Kalshaneh outcrop, a core of an exploration borehole, focused on coal seams in the lowermost part of the Hojedk Formation, near to the measured outcrop section, was incorporated into this study to better characterize the facies and their vertical relationship and lateral variations.…”
Section: Methodsmentioning
confidence: 99%
“…Although the Kalshaneh outcrop provides an exceptional two-dimensional exposure of the sedimentary facies relationships, a core section provides fresh and continuously drilled rocks, and thus integrated surface and subsurface data complement palaeoenvironmental reconstructions (e.g. Salehi et al 2015;Glad et al 2018;Wilmsen & Bansal, 2021). To supplement the facies analysis in the Kalshaneh outcrop, a core of an exploration borehole, focused on coal seams in the lowermost part of the Hojedk Formation, near to the measured outcrop section, was incorporated into this study to better characterize the facies and their vertical relationship and lateral variations.…”
Section: B Subsurface Datamentioning
confidence: 99%
“…The Langenstein glauconites are highly evolved, well-preserved, and have been formed soon after sediment deposition (i.e., ~0.1 to ~1 Ma; average: ~0.3 ± 0.5 Ma), as determined by the difference in the bio-stratigraphic and corrected glauconite age (see Figure 6), which calls for fast glauconitization immediately at the sediment-seawater interface and continuous supply of key elements, such as K, Mg, Al, Si, and Fe [19]. Recently, Wilmsen and Bansal [23] have basically drawn the same conclusion based on a study of Cenomanian glauconites from the Elbtal Group (Saxony, eastern Germany), which formed within ≤0.4 Ma in a nearshore siliciclastic depositional system. They argue that glauconite formation occurred under warm conditions on rather short time scales and under, in part, high accumulation rates and thus under environmental conditions fundamentally different from recent ones.…”
Section: Timing Of Glauconite Formationmentioning
confidence: 98%
“…To illustrate, according to Odin and Matter [13], evolved glauconite requires ~10 5 to 10 6 years to form in permeable shelfal sediments, whereas Meunier and El Albani [22] argue that glauconite formation proceeds more slowly in less permeable or deep-marine lithologies, requiring a maturation lasting a few million years (~5 Ma). Recent work on glauconite authigenesis in shallow-water [23] vs. deep-marine [17] settings basically support both interpretations, with slower formation rates potentially problematic for glauconite-based geochronology and a precise dating of marine sediments or sedimentary rocks.…”
Section: Introductionmentioning
confidence: 97%
“…The "ideal" location for the authigenic formation of this mineral is therefore often considered to be the distal edge of the continental shelf. Alongside this common view, numerous studies have reported that glauconite could also appear in shallow environments, such as estuaries or deltas, or even river environments [e.g., El Albani et al, 2005, Meunier andEl Albani, 2007, andreferences therein;Wilmsen andBansal, 2021, Bansal et al, 2022]. Therefore, the speed of formation of glauconite can also be questioned: if the formation of this mineral is possible in proximal environments, where sedimentation rates can be high, then the contact time between authigenic minerals and seawater column cannot be extremely long [Wilmsen and Bansal, 2021].…”
Section: Introductionmentioning
confidence: 99%